2011
DOI: 10.1016/j.humov.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to mechanical foot stimulation during human locomotion under body weight support

Abstract: a b s t r a c tInput from the foot plays an essential part in perceiving support surfaces and determining kinematic events in human walking. To simulate adequate tactile pressure inputs under body weight support (BWS) conditions that represent an effective form of locomotion training, we here developed a new method of phasic mechanical foot stimulation using light-weight pneumatic insoles placed inside the shoes (under the heel and metatarsus). To test the system, we asked healthy participants to walk on a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 59 publications
(77 reference statements)
1
25
0
1
Order By: Relevance
“…The quickly adapting mechanoreceptors provide information about pressure amplitude and changes in pressure exerted on the skin, causing rapid motor changes of posture for postural control 21) . However, this study found that the loss of proprioception due to paralysis 22) and subsequent lowering of proprioception in stroke patients cause an increased span of postural sway compared with that in normal persons. This study measured the postural sway velocity, area, and distance using a forceplate with the aim of exploring the influence of an unstable surface on the postural sway in the standing posture.…”
Section: Discussionmentioning
confidence: 57%
“…The quickly adapting mechanoreceptors provide information about pressure amplitude and changes in pressure exerted on the skin, causing rapid motor changes of posture for postural control 21) . However, this study found that the loss of proprioception due to paralysis 22) and subsequent lowering of proprioception in stroke patients cause an increased span of postural sway compared with that in normal persons. This study measured the postural sway velocity, area, and distance using a forceplate with the aim of exploring the influence of an unstable surface on the postural sway in the standing posture.…”
Section: Discussionmentioning
confidence: 57%
“…The benefit of gait training using a BWS system is not only simply supporting the subject's body weight during walking but also the improvement of other gait parameters such as ground reaction force, hip, knee, and ankle angle parameters, and the symmetry of gait locus. [5][6][7][8] Recently, the BWS system has been combined with leg robotic orthoses such as Locomat, task activity, which allow patients to initiate gait training activities early after injury. 3 The gait training process for incompletely healed patients normally undergoes many periods, depending on the condition of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…All three major lower limb segments (thigh, shank, foot) contribute to the co-variance of angular motion and to appropriate limb axis length and orientation ('telescopic limb') behavior resulting in a gait-dependent center-ofmass trajectories . Although the force of gravity acts on both the stance and swing limb (Mochon and McMahon 1980;Kuo 2001;Doke et al 2005;Doke and Kuo 2007;Raichlen 2008), most of these studies used reduced gravity simulators that unload the body only during the stance phase Griffin et al 1999;Ivanenko et al 2002;McCrory et al 2002;Gravano et al 2011) under the assumption that the swing limb adapts automatically to the modified gait. However, to what extent is this true?…”
Section: Introductionmentioning
confidence: 99%